SISTEM INFORMASI AKTIVITAS PEGAWAI TERPADU UNIVERSITAS SAHID SURAKARTA - Pangemanan, Riskyanto; Anwariningsih, Sri Huning; Susilo, Dahlan (2086-4221, 2013)
The role of information is increasingly needed to support an activity. In line with the development of information technology both hardware and software is rapidly increasing, then it should be an institution  can take advantage of advances in information technology. One form of utilization is for the development of information systems that can support the activities of employees in making a decision. With this system, the activity of employees in an institution can be optimally and efficiently so as to increase productivity.  Integrated Activity  Information  Systems  Employee of  Sahid Surakarta University  is a software  for data processing  activities of  employees  and lecturer university  Sahid  Surakarta. Functions that  any  activities at  the University of Sahid Surakarta both outside and inside the campus can be controlled so as to minimize conflict of schedule.